Etograma e protocolo para o condicionamento do papagaio-de-cara-roxa (Amazona brasiliensis) mantido em cativeiro - Santos, Ana Cláudia Marera dos (2019)
Ethology has played an important role in the conservation of fauna in the recent years. Nowadays, behavioral studies help in situ and ex situ conservation actions, becoming an essential tool for reproduction and reintroduction projects, as well as for the management of captive handling and welfare promotion, which have two main goals: the environmental enrichment and the operant conditioning, both of which are highly dependent on the information contained in the species' ethogram. Thus, considering that there is little ethological information about the species Amazona brasiliensis, a parrot threatened with extinction, the present study aimed to describe the ethogram of the species in captivity, from 82 hours of sample effort based on the ad libitum method, resulting in the description of 58 behaviors. It also developed a conditioning protocol for veterinary management, based on 10 pilot training sessions. Thus, tThus, the work resulted in increased ethological knowledge about the species Amazona brasiliensis, to suggest measures to improve ex situ maintenance, aimed at reducing stress during veterinary procedures